Synthesis and Properties of NaSICON‐type LATP and LAGP Solid Electrolytes - DeWees, Rachel; Wang, Hui (ChemSusChem, 2019)
Inorganic solid electrolytes play a critical role in solid‐state lithium batteries achieving high safety levels and high energy densities. The synthetic approaches to solid electrolytes are important for both fundamental research and practical applications. Li1+xAlxTi2−x(PO4)3 (LATP) and Li1+xAlxGe2−x(PO4)3 (LAGP) are two representative solid electrolytes with a sodium superionic conductor (NaSICON) structure. Herein, LATP and LAGP solid electrolytes are reviewed from the synthesis perspective, and correlated with their structure and conductive properties, as well as their electrochemical applications in batteries. First, the solid‐ and liquid‐based synthetic methods to LATP and LAGP solid electrolytes and the key influencing factors are described. Second, the crystal structures and phase purities obtained from different synthetic approaches are introduced. Third, the conductive mechanisms, composition effects, and synthetic effects on the conductivities of LATP and LAGP solid electrolytes are compared. Fourth, the electrochemical applications of these two solid electrolytes in full batteries are discussed, including roles as solid electrolytes, composite components in electrodes, and surface coatings on electrodes. In the last section, a brief outlook is provided on the future development of NaSICON‐type solid electrolytes for all‐solid‐state batteries. How was it made? Li1+xAlxTi2−x(PO4)3 (LATP) and Li1+xAlxGe2−x(PO4)3 (LAGP), which are popular sodium superionic conductor (NaSICON)‐type solid electrolytes, are reviewed from the perspective of their synthesis. The synthetic methods have been correlated with the structures and conductive properties. Electrochemical applications of these electrolytes in batteries are also presented.